MOTIVATION OF PUBLIC AUTHORITIES EMPLOYEES TO WORK - Kirieiev , Yevhen (Theory and Practice of Public Administration, 2019)
In the process of managing work potential development, an important role is played by ensuring that employees are properly motivated, in particular, to achieve high individual, organizational and social results. The mechanism of motivation is constantly changing under the influence of external factors, has specific differences for each organization, requires constant regulation. Its peculiarities in public administration are related to the specific work and imperativeness of the public service institute. Such a mechanism is mainly based on incentives related to the clear regulation of the public authorities employees work and is a complex system of relations between them. The purpose of the work is to determine the essence, basic concepts and mechanisms of the process of motivation of employees of public administration in modern conditions. The motivation essence lies in the fact that the subject of motivational relationships is an individual with a set of potential needs, which selects a certain type of behavior depending on his motivational attitudes, on the consciousness of which acts as a set of external and internal factors, and various influences. The analysis of international experience shows that in most countries new technologies of personnel management are introduced, the principles of management aimed at improving the performance of public authorities’ employees: rating system of personnel evaluation, system of payment for results etc. An analysis of the crisis management experience has revealed that the tools of resolving the contradictions in labour are the correlation of the position and the salary with the length of service, as well as increasing the remuneration for efficient and effective activity. World practice has accumulated a sufficient base of tools in the field of labour relations management and labour organization. These tools are differently effective in different situations, capturing changes in the organization of remuneration, in the organization of labour itself, in labour management, in changes in the qualifications of employees. It is determined that this practice can also be used in the process of public service reforming in Ukraine, which is conducted to ensure high rates of country socio-economic development. The expediency of applying A. Maslow’s theory in the public authorities practice based on consideration of motivational influence on employees depending on the dominant needs of the individual has been proved.